PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN MOTIVASI TERHADAP KINERJA KARYAWAN BMT NU - Nuzulul Qurnain (Assyarikah: Journal of Islamic Economic Business, 2022)
Leadership is a dominant and crucial role in the overall effort to improve performance both at the individual, group and organizational levels. A successful leader is a leader who is able to carry out leadership tasks effectively to achieve organizational goals, besides giving motivation to employees by giving grades can also improve employee performance. This study aims to determine the effect of democratic leadership style and motivation on the performance of the employees of the BMT NU Branch of Galis Pamekasan. This type of research is a quantitative research. Types and sources of data in this study in the form of qualitative data and quantitative data. The sample in this study amounted to 12 people. This research consists of 2 independent variables, namely democratic leadership style (X1) and motivation (X2), and the dependent variable is employee performance (Y). Testing data instruments with Validity Test, Reliability Test. While the analysis technique in this study uses the F test and t test. The first result of this research is that democratic leadership style affects employee performance, and the second is that motivation affects employee performance.